2019
DOI: 10.5194/wes-4-251-2019
|View full text |Cite
|
Sign up to set email alerts
|

Power curve and wake analyses of the Vestas multi-rotor demonstrator

Abstract: Abstract. Numerical simulations of the Vestas multi-rotor demonstrator (4R-V29) are compared with field measurements of power performance and remote sensing measurements of the wake deficit from a short-range WindScanner lidar system. The simulations predict a gain of 0 %–2 % in power due to the rotor interaction at below rated wind speeds. The power curve measurements also show that the rotor interaction increases the power performance below the rated wind speed by 1.8 %, which can result in a 1.5 % increase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 33 publications
3
46
0
Order By: Relevance
“…(3), d should be equal to 40m for the MR4 case. The value of rotor spacing s is selected to be 0.1d, inspired by the multi-rotor turbine concept demonstrator previously installed by Vestas Wind Systems A/S at DTU Risø campus 13 .…”
Section: A Detailed Comparison Of Turbine Wakes: Mr Versus Sr Turbinesmentioning
confidence: 99%
See 1 more Smart Citation
“…(3), d should be equal to 40m for the MR4 case. The value of rotor spacing s is selected to be 0.1d, inspired by the multi-rotor turbine concept demonstrator previously installed by Vestas Wind Systems A/S at DTU Risø campus 13 .…”
Section: A Detailed Comparison Of Turbine Wakes: Mr Versus Sr Turbinesmentioning
confidence: 99%
“…Moreover, due to the representation of turbines using the standard actuator-disk model, effects of turbine-induced flow rotation were dismissed. Recently, van der Laan et al 13 have studied the wake flow behind the multi-rotor turbine demonstrator installed by Vestas Wind Systems A/S. In particular, using Reynolds-averaged Navier-Stokes (RANS) simulations, they showed that the multi-rotor wind turbine wake recovers faster compared to the wake of a single-rotor wind turbine with an equivalent rotor diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from the INNWIND project showed the potential of a 20 MW MRS with 45 rotors to reduce the levelized cost of energy (LCoE) compared to a power equivalent single rotor (SR) (Jamieson et al, 2017). Recent results from Vestas' four rotor MRS demonstrator revealed advantages in aerodynamic efficiency and in wake recovery when compared to a SR (van der Laan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a constant and uniform thrust coefficient is applied to all four rotors of the 4-rotor turbine. The controller adopted in van der Laan et al (2019), on the other hand, allowed for small variations of up to 5 % in the thrust coefficients of the lower and upper rotors. Second, the dimensions 60 of the turbines are different in the two studies.…”
mentioning
confidence: 99%
“…Second, the dimensions 60 of the turbines are different in the two studies. Assuming a typical value of 1000 m for the boundary layer height, the rotors of the 4-rotor turbines in the present study have a diameter of 50 m, which is approximately 1.7 times that of the 4R-V29 turbine considered in van der Laan et al (2019). Finally, only isolated 4-rotor turbines are considered in van der Laan et al (2019), while interactions between multiple 4-rotor turbines is studied in this paper.…”
mentioning
confidence: 99%